First Principles Calculations on the Stoichiometric and Defective (101) Anatase Surface and Upon Hydrogen and H2Pc Adsorption: The Influence of Electronic Exchange and Correlation and of Basis Set Approximations - Martínez-Casado, Ruth; Todorović, Milica; Mallia, Giuseppe; Harrison, Nicholas M.; Pérez, Rubén (Frontiers in Chemistry, 2019)
Anatase TiO2 provides photoactivity with high chemical stability at a reasonable cost. Different methods have been used to enhance its photocatalytic activity by creating band gap states through the introduction of oxygen vacancies, hydrogen impurities, or the adorption of phthalocyanines, which are usually employed as organic dyes in dye-sensitized solar cells. Predicting how these interactions affect the electronic structure of anatase requires an efficient and robust theory. In order to document the efficiency and accuracy of commonly used approaches we have considered two widely used implementations of density functional theory (DFT), namely the all-electron linear combination of atomic orbitals (AE–LCAO) and the pseudo-potential plane waves (PP–PW) approaches, to calculate the properties of the stoichiometric and defective anatase TiO2 (101) surface. Hybrid functionals, and in particular HSE, lead to a computed band gap in agreement with that measured by using UV adsorption spectroscopy. When using PBE+U, the gap is underestimated by 20 % but the computed position of defect induced gap states relative to the conduction band minimum (CBM) are found to be in good agreement with those calculated using hybrid functionals. These results allow us to conclude that hybrid functionals based on the use of AE–LCAO provide an efficient and robust approach for predicting trends in the band gap and the position of gap states in large model systems. We extend this analysis to surface adsorption and use the AE–LCAO approach with the hybrid functional HSED3 to study the adsorption of the phthalocyanine H2Pc on anatase (101). Our results suggest that H2Pc prefers to be adsorbed on the surface Ti5c rows of anatase (101), in agreement with that seen in recent STM experiments on rutile (110).